Depression, Anxiety and Stress among Nursing Students at Biratnagar - Chapagain, Sita; Neupane, Saraswata; Pokhrel, Indira; Kafle, Tara Kumari (Journal of Nobel Medical College, 2023)
Background: Nursing students’ depression, anxiety and stress are important issue in society with strongest connection to client recover when these students become nurse in future.Such psychological distress among them leads to less productivity, reduced quality of life, learning difficulties and may negatively affect patient care. Materials and Methods: A descriptive, cross-sectional study was conducted in Nobel Medical College Teaching Hospital, Biratnagar. A total of 104 Bachelor nursing students were selected by using a non-probability total enumerative sampling technique. Data were collected in the classroom through self-administered questionnaire using standardized tool DASS-21. All calculations and statistical analyzed by using SPSS software version 23.0. Results: The mental health status of nursing students reported alarming accounting about 37% severe anxiety, 17% severe depression and severe stress each. Among the six variables run, only year of study found associated with depression, however, stress and anxiety were not found associated with all given six variables. Similarly, there is very strong positive correlation was found among stress, anxiety and depression. Conclusion: The number of students experiencing depression, anxiety and stress were some levels. Among the six variables run, only year of study found associated with depression but none of the variables found associated with other mental health dimensions. Similarly, the dimension of mental health: stress, anxiety and depression were found strongly correlated.